Determinants of stock returns : Singapore case. - Tan, Keng Wee. (2008)
Making use of an expected return factor model, we incorporate several factors from the study by Haugen and Baker (1996), and establish the relevance of these chosen factors in forecasting returns for stocks traded in Singapore by introducing a multifactor model that will measure stock returns.